Pushing for speed or scope? Pharmaceutical lobbying and Food and Drug Administration drug review. (2nd April 2019) - Barber, Benjamin; Diestre, Luis
Abstract : Research Summary: We argue firms implementing political activities face a fundamental trade‐off between the content and the speed of public officials' decisions. Firms can use their political capital to speed up public officials' decisions at the expense of less customized content, or to push for more tailored content at the expense of speed. How do firms respond to this trade‐off? We argue firms' nonmarket strategies are determined by their market environment: they will push for content or speed depending upon the level of competitive pressures they face in the market. In the presence of high market pressures, firms are more likely to push for speed; whereas firms facing low market pressures are more likely to push for customized content. Managerial Summary: We show evidence of a trade‐off between content and speed in the political arena looking at Food and Drug Administration (FDA) drug approvals: lobbying for broader drugs leads to longer revisions, whereas lobbying to speed up the review process leads to narrower drugs. We explore how firms respond to this trade‐off in a sample of 540 new drug applications to the FDA from 1998 to 2015. We show firms' lobbying strategies depend upon the level of intellectual property (IP) protection behind their drugs: firms with high levels of IP protection are more likely to lobby for drug scope, whereas firms with low levels of IP protection are more likely to lobby for revision speed.